Systematic Literature Review: Membandingkan Pendekatan Metode Agile dan Waterfall Dalam Pengembangan Perangkat Lunak - Widyantoro, Aries; Faradisa Al Bina, Fiqhy; Prayoga, Teddy; Safei, Robi; Akmal Arrasid, Muhammad (Journal of Comprehensive Science, 2025)
Software development is a complex and ever-evolving process. The selection of the right methodology is crucial in determining the success of the project. Among the various methodologies that exist, the Agile and Waterfall approaches have been the two most frequently compared. This study aims to conduct a systematic review of the literature (SLR) of various studies that compare the two approaches. This research was conducted by identifying and analyzing a number of relevant scientific articles from various databases. Strict inclusion and exclusion criteria are applied to ensure the quality of the data used. The data analysis process is carried out by identifying the main themes, comparing the findings of various studies, and developing a comparative framework between the Agile and Waterfall approaches. The results of the research and analysis show that the choice between the Agile and Waterfall approaches is highly dependent on the specific context of the project. The Agile approach is more suitable for projects with frequently changing requirements, small and collaborative teams, and an emphasis on fast product delivery. In contrast, the Waterfall approach is more suitable for projects with clear and stable requirements, large and structured teams, and an emphasis on careful planning. In addition, the study also identifies a number of contextual factors that can influence the successful implementation of both approaches, such as organizational size, organizational culture, and project complexity.